Analysis of The Influence of Financial Literacy, Investment Motivation, and Religiosity on Investment Interest in Sharia Shares - Hidayat, Agung (Journal of Applied Management and Business, 2024)
This research aims to analyze and find evidence empirical research regarding the influence of financial literacy, investment motivation, and religiosity on investment interest in sharia shares. This research is quantitative research with data collection techniques using questionnaires. The sample was 110 respondents who were students majoring in accounting at the Semarang State Polytechnic. The sampling technique used was simple random sampling by distributing questionnaires (randomly) to students majoring in accounting at the Semarang State Polytechnic. Primary data processing uses instrumental test analysis methods, classical assumptions, multiple linear regression, and hypothesis testing. The results of this study indicate that financial literacy does not have a significant positive effect on interest in investing in sharia shares, investment motivation has a positive and significant effect on interest in investing in sharia shares, and religiosity has a positive and significant effect on interest in investing in sharia shares.